Welding or Adhesive Bonding — is this a question for the future? - Reisgen, U.; Schleser, M. (Автоматическая сварка, 2013)
Modern light-weight structures are composed of most different materials. The joining of these materials with and among one another requires the application of different joining techniques with the focus on welding and adhesive bonding. In this paper, the advantages of both methods are discussed and possibilities for the combined application of welding and bonding techniques are presented.